A new species of Lepidodactylus (Squamata: Gekkonidae) from the mountains of northeastern Papua New Guinea: older than the hills - Kraus, Fred; Oliver, Paul M. (Zootaxa, 2020)
We describe a new species of Lepidodactylus with an unusual distribution across scattered localities in three isolated mountain ranges of northeastern New Guinea. It is a member of the Lepidodactylus pumilus group and can be distinguished from all other Melanesian Lepidodactylus by aspects of size, scalation, digital webbing, and coloration. Previously published genetic and morphological data indicate that the new species is most similar to Lepidodactylus magnus, but it diverged from this species and other close relatives in the mid-Miocene or earlier, potentially on islands of the former South Caroline Arc. Estimated divergence dates between the new species and its sister taxon suggest that cladogenesis occurred before the uplift of the mountains that they currently inhabit. Recent systematic work also emphasizes an apparent pattern of increasing body size with elevation in species from the Lepidodactylus pumilus group from northeastern New Guinea, with the largest species occurring in montane habitats where few or no other gecko species are known. Both lines of evidence are consistent with an existing hypothesis that the Lepidodactylus pumilus group is an old insular lineage within which contemporary species diversity and distributions have been strongly shaped by low ability to effectively compete against other aggressive geckos in species-rich lowland rainforests. The role that biotic interactions may have played in shaping tropical gecko communities along elevational gradients warrants further investigation.